Novel Small-Molecule Troponin Activator Increases Cardiac Contractile Function Without Negative Impact on Energetics. (8th November 2021) - He, Huamei; Baka, Tomas; Balschi, James; Motani, Alykhan S.; Nguyen, Kathy K.; Liu, Qingxiang; Slater, Rebecca; Rock, Brooke; Wang, Chen; Hale, Christopher; Karamanlidis, Georgios; Hartman, James J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Current heart failure therapies unload the failing heart without targeting the underlying problem of reduced cardiac contractility. Traditional inotropes (ie, calcitropes) stimulate contractility via energetically costly augmentation of calcium cycling and worsen patient survival. A new class of agents—myotropes—activates the sarcomere directly, independent of calcium. We hypothesize that a novel myotrope TA1 increases contractility without the deleterious myocardial energetic impact of a calcitrope dobutamine. Methods: We determined the effect of TA1 in bovine cardiac myofibrils and human cardiac microtissues, ex vivo in mouse cardiac fibers and in vivo in anesthetized normal rats. Effects of increasing concentrations of TA1 or dobutamine on contractile function, phosphocreatine and ATP concentrations, and ATP production were assessed by 31 P nuclear magnetic resonance spectroscopy on isolated perfused rat hearts. Results: TA1 increased the rate of myosin ATPase activity in isolated bovine myofibrils and calcium sensitivity in intact mouse papillary fibers. Contractility increased dose dependently in human cardiac microtissues and in vivo in rats as assessed by echocardiography. In isolated rat hearts, TA1 and dobutamine similarly increased the rate-pressure product. Dobutamine increased both developed pressure and heart rate accompanied by decreased phosphocreatine-to-ATP ratio and decreased free energy of ATP hydrolysis (ΔG~ATP ) and elevated left ventricular end diastolic pressure. In contrast, the TA1 increased developed pressure without any effect on heart rate, left ventricular end diastolic pressure, phosphocreatine/ATP ratio, or ΔG~ATP . Conclusions: Novel myotrope TA1 increased myocardial contractility by sensitizing the sarcomere to calcium without impairing diastolic function or depleting the cardiac energy reserve. Since energetic depletion negatively correlates with long-term survival, myotropes may represent a superior alternative to traditional inotropes in heart failure management.